Real-Time Feedback on Consumer's Behavior: Literature Review - Nabeel, Muhammad; Ali, Basel; Hamdan, Allam (International Journal of Energy Economics and Policy, 2019)
Effective energy management can provide an important tool to reduce energy consumption, which is crucial in the fight to protect natural resources and to have a clean environment. Reducing energy consumption can be achieved by reducing energy waste in residential building. Waste in energy can be a result of using energy wasting appliances as well as reckless human behavior such as not turning off unwanted electrical appliances or operating air conditioners or heaters at unnecessary temperature settings, just to name a few. This paper reviews a couple of studies which was conducted on the use of real-time feedback technology to improve energy consumption behavior and habits. The methodologies used will be described along with the results of each study. A list of challenges and limitations of such studies will be explained. The review should give guidance and recommendations on how to conduct a study on the use of real-time feedback technology. Using these recommendations, a study on the topic was conducted by one of the authors in the Kingdom of Bahrain. The results of the study are briefly described in the paper. Keywords: Real-Time Feedback, Consumer's Behavior, energy management JEL Classifications: Q43, Q47, Q53 DOI: https://doi.org/10.32479/ijeep.8353